A Study of Improving Independent Walking Outcomes in Children Who Are Blind or Have Low Vision Aged 5 Years and Younger. (July 2022) - Ambrose-Zaken, Grace
Walking alone (without assistance) is considered by the World Health Organization as the terminal independent walking milestone, typically achieved by 18 months. Children born with severe visual impairment and blindness (visual impairments) do not achieve independent walking milestones on time. This study examined independent walking in 35 children with visual impairments (VIs) aged 14–69 months. Before treatment, they had limited to no anticipatory control. Wearing the pediatric belt cane (PBC) provided them with consistent, tactile anticipatory control. Thirty-five participants with VIs' independent walking milestones were analyzed using pre- and post-video recordings provided weekly 1 month before and the 3 months after obtaining the PBC. The PBC consisted of a rectangular frame that connects to a custom-made belt with magnets. The PBC provided no weight support. While none of the participants had motor impairments, 80% of them were receiving physical therapy services prior to obtaining a PBC. Fifty-four percent were receiving orientation and mobility services, and half were equipped with hand-held mobility tools (long canes, adaptive mobility devices, push toys, and reverse walkers). A paired samples t -test indicated a significant difference between the before and with PBC scores ( N = 35, t = −13.0, df = 34, p = .000). Participants demonstrated significantly improved independent walking after wearing their PBC regularly over 3 months. Before PBC, the participants demonstrated delayed independent walking milestones. Most participants walked only with assistance. Those who walked independently experienced unavoidable bodily collisions and used a slow pace with poor gait patterns. After being provided PBCs, these same participants' independent walking milestones improved, all but three were walking independently and five were observed independently running. Wearing their PBCs allowed them to perform motor skills, like running, often described as needing to be specifically taught to learners with VIs due to their inability to learn incidentally through visual observation.